1998
DOI: 10.1177/002215549804601014
|View full text |Cite
|
Sign up to set email alerts
|

A New Immunocytochemical Technique for Ultrastructural Analysis of DNA Replication in Proliferating Cells After Application of Two Halogenated Deoxyuridines

Abstract: SUMMARYWe describe a colloidal gold immunolabeling technique for electron microscopy which allows one to differentially visualize portions of DNA replicated during different periods of S-phase. This was performed by incorporating two halogenated deoxyuridines (IdUrd and CldUrd) into Chinese hamster cells and, after cell processing, by detecting them with selected antibodies. This technique, using in particular appropriate blocking solutions and also Tris buffer with a high salt concentration and 1% Tween-20, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 24 publications
5
29
0
Order By: Relevance
“…In addition, we verified that only one size of gold particles was present following incubation of sections in the presence of only rat anti-BrdU (or mouse anti-BrdU) and then in the presence of a mixture of 6-nm gold labeled anti-mouse antibody and 10-nm gold labeled anti-rat antibody. Finally, in both optical and ultrastructural studies, we verified that the Harlan Sera-Lab rat anti-BrdU does not recognize IdUsubstituted DNA, while conversely mouse Becton Dickinson anti-BrdU does not recognize CldU-substituted DNA, as previously reported (Alten et al, 1992;Jaunin et al, 1998).…”
Section: Ultrastructural Studiessupporting
confidence: 83%
See 3 more Smart Citations
“…In addition, we verified that only one size of gold particles was present following incubation of sections in the presence of only rat anti-BrdU (or mouse anti-BrdU) and then in the presence of a mixture of 6-nm gold labeled anti-mouse antibody and 10-nm gold labeled anti-rat antibody. Finally, in both optical and ultrastructural studies, we verified that the Harlan Sera-Lab rat anti-BrdU does not recognize IdUsubstituted DNA, while conversely mouse Becton Dickinson anti-BrdU does not recognize CldU-substituted DNA, as previously reported (Alten et al, 1992;Jaunin et al, 1998).…”
Section: Ultrastructural Studiessupporting
confidence: 83%
“…These data suggested that BCL6 bodies are associated with replicating DNA and/or that their close vicinity is a nuclear micro-environment prone to support DNA replication, and raised the possibility that they influence the replication foci (RF) assembly, positioning, or activity (Albagli et al, 2000). Moreover, together with the proposed spatial coincidence or close apposition between transcription and replication sites in nucleus (Fakan and Nobis, 1978;Jaunin et al, 1998Jaunin et al, , 2000Wei et al, 1998), these previous data led us here to also compare the localization of BCL6 bodies and RNA.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Cl-and Icontaining deoxyuridine has been used for DNA double labeling in pulse-chase experiments (Jaunin et al 1998). …”
mentioning
confidence: 99%